IMPROVING INVENTORY MANAGEMENT AND FORECASTING SYSTEM IN PT XYZ - Nirvana, Kinanti; Lestari, Yuliani Dwi (Journal of Business and Management, 2018)
Abstract. PT.XYZ, as one of fashion retailer in Bandung is facing issue on how to optimize their operation management. Currently, the company does not have any proper calculation on determining how much stock they needed, level of stock should be maintain, the appropriate time to reorder the stock and any system to forecast the future demand. That condition makes overstock and stockout occur in the company. This study is conducted in order to identify the root cause of inventory management issue and design the appropriate policy for inventory management and forecasting system in PT. XYZ. The study is conducted by using qualitative and quantitative analysis. No system to determine the appropriate stock, order quantity, and the time to reorder stock, no system to forecast the demand are causes of inventory management issue in PT.XYZ. Economic Order Quantity (EOQ) model is used to determine the new order quantity, and probabilistic and safety stock model to determine the reorder point (ROP) and minimum stock. The analysis finds out that the new proposed system can reduce the number of shortage, overstock, and decrease the total inventory cost.Keywords: Forecasting, Inventory Management, Economic Order Quantity, Reorder Point, Probabilistic Model